Translation of Pseudomonas aeruginosa Bacteriophage PP7 RNA by a Cell-Free Amino Acid Incorporating System from Escherichia coli - Bassel, B. A. (1974)
We have compared the activities of the RNA genomes of Pseudomonas aeruginosa phage PP7 and coliphages Qβ and f2 in a cell-free amino acid incorporating system derived from Escherichia coli. The rate of incorporation of [(14)C]leucine in the PP7 RNA-directed system is greater than in the systems directed by either Qβ or f2 RNA. The response to changes in phage RNA concentrations is similar in all the systems, reaching a saturation level at 0.75 to 1.0 mg of RNA per ml of reaction mixture. Analysis of complete reaction mixtures of the PP7 RNA and of the Qβ RNA systems by sucrose gradient centrifugation shows generally similar patterns for both RNAs. The principal differences are that in the PP7 system a slightly higher percentage of RNA forms ribosome complexes and that the polysomes are somewhat smaller. PP7 RNA is also degraded more extensively during the reaction than is Qβ RNA. Analysis of the products of the reactions by acrylamide gel electrophoresis shows that PP7 coat protein is the only identifiable product of the PP7 RNA-directed system, suggesting that only the coat protein cistron is translated by E. coli ribosomes.